صفات القيادة الجيدة ودورها في تطوير الإدارة في الفكر الإسلامي: دروس مستفادة من نموذج عبد الملك بن مروان = Qualities of good leadership and its role in the development of management in Islamic thought: “lessons learned from the model of 'Abd Al-Malik Ibn Marwan" = Kualiti kepimpinan yang baik dan peranannya dalam pembangunan pengurusan dalam pemikiran Islam: "pengajaran yang dipetik daripada model 'Abd Al-Malik Ibn Marwan - Baraami, Khalid Ali Bakhit; Abdelaziz, Berghout (IIUM Press, 2023)
The study aimed to analysethe qualities of good leadership, and its role in developing management in Islamic thought: "A Study of the Model of Abdul Malik bin Marwan", as well as the most prominent features of successful administrative leadership during his reign. It shows the impact of successful administrative leadership in developing management andmentions some aspects of benefiting from this model in our contemporary reality. The study followed the descriptive-analytical approach through induction and textual analysis andconcluded that Caliph Abdul Malik bin Marwan presented a distinguished model of administrative leadership, developed and revitalised the administrative apparatus, and arabised management, which is known as the arabisation movement. The study recommended the necessity of deepening studies and research in these leadership and administrative aspects of Islamic thought to disseminate them and benefit from them in our current situation.